PENGARUH PENAMBAHAN SISTEM IOT RASPBERRY PI TERHADAP KECEPATAN CETAK DAN TINGKAT PRODUKTIVITAS OPERATOR 3D PRINTER REPRAP - I Putu Ade Chandra Priyatna; I G A P Raka Agung; Yoga Divayana (Jurnal SPEKTRUM, 2021)
Most of desktop-scale 3D printers are based on the open-source design of the ReplicatingRapid Prototyper (REPRAP) community. One aspect that can be developed in REPRAP 3Dprinters is the addition of Internet of Things (IoT) technology. Therefore, a Raspberry Pi-based IoTsystem that can be implemented on a REPRAP 3D printer is developed. The IoT system allowsthe 3D Printer to connect into internet network and has a website-based interface. This study aimsto compare the impact of Raspberry Pi based IoT systems implementation on the 3D printingspeed and to measure productivity level of 3D printer operator. Testing is done by printing fourobjects when the IoT system has not been added to the 3D printer and printing four objects whenthe IoT system has been added to the 3D printer. In testing, the data on the printing time of eachobject is obtained, this data is used to compare the print speed between before and after the 3Dprinter was added to the IoT system. Furthermore from testing, the data of time required byoperators to prepare and monitor the performance of 3D printers is also obtained, this data is usedto compare the productivity levels of 3D printer operators before and after adding the IoT system.Based on the test results, it was found that 3D printers with IoT systems have faster printpreparation times than 3D printers without IoT systems. However, 3D printers with IoT systemshave a longer machine time than 3D printers without IoT systems. The operator productivity levelfor 3D printers with IoT systems is higher than 3D printers without IoT systems.